Removal of 2, 4, 6 trichlrophenol from simulated wastewater via progressive freeze concentration: effect of initial concentration with the usage of response surface methodology as the means of optimization: article - Mazzam, Anwar Addini; Jamal Ikhsan, Ikhmal Zariq Al Imran; Bakar, Muhammad Noor Faqeh; Hamizlan, Hariz Asyraf; Ab. Hamid, Farah Hanim (2020)
2, 4, 6-Trichlorophenol (TCP) has been used primarily in various pesticide formulations and as a wood preservative. Only the slightest amount of TCP in wastewater is harmful and it can be the cause of many diseases, thus the importance to remove the TCP from wastewater is imminent. In this study, Progressive Freeze Concentration (PFC) was used to remove TCP from a simulated wastewater.